Sinergitas Aparat Penegak Hukum Dalam Memberantas Tindak Pidana Korupsi Di Indonesia - Sururoh, Yeni Lin; Sadino, Sadino; Rifai, Anis (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Currently, investigations into criminal acts of corruption in Indonesia are carried out by the Corruption Eradication Commission (KPK), the Police and the Attorney General's Office. The three institutions have the authority to investigate corruption. This is regulated in Article 3 paragraph (1) Memorandum of Understanding Between the Corruption Eradication Commission, the Attorney General's Office, and the Police Number: SPS-97/01-55/03/2017, Number: KEP-087/A/JA/03/2017, Number : B/27/III/2017 dated 29 March 2017 However, in practice, these provisions do not work as they should, such as overlapping duties and authorities. There are 3 discussions of issues that are focused on in this study, namely how is the system for eradicating corruption in Indonesia's current positive law? what is the concept of a synergy system carried out by law enforcement officials (KPK, Police and Prosecutors' Office) in eradicating criminal acts of corruption in Indonesia? And what is the strategy of the Indonesian government in eradicating criminal acts of corruption in the future? The conclusion in this study is that the government together with the legislature has created a legal instrument that is used to eradicate criminal acts of corruption which is embodied by Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning Amendments to Laws -Law No. 31 of 1999 concerning Eradication of Corruption Crimes. Several integration systems that can be carried out by the Attorney, Police and Corruption Eradication Commission in eradicating corruption include establishing an inter-institutional interaction system, establishing an operational work system and mechanism as well as establishing a monitoring and development system. The Indonesian government's strategy to prevent corruption in the future can be carried out through the integrity system within the scope of the KPK, the Police and the Attorney General's Office. Besides that, the KPK also has a special strategy in Corruption Eradication for the vision of Indonesia free from corruption, this strategy is known as the Trisula strategy, namely law of enforcement, law of prevention and law of education.